Pendidikan IPS dalam Memahami Perubahan Sosial melalui Berpikir Kritis untuk Menghadapi Fenomena Cancel Culture - Khairunniza, Liza Dwi Eftiza; Abdulkarim, Aim (Pedagogi: Jurnal Ilmu Pendidikan, 2025)
In an increasingly digitalized and globalized world, social studies education plays a pivotal role in shaping students’ critical thinking and understanding of social change. This study explores how social studies can be a platform for addressing contemporary issues, particularly the phenomenon of Cancel Culture. By referring to sources indexed in Scimago Journal & Country Rank (SJR) and Science and Technology Index (SINTA), the research emphasizes the urgency of integrating innovative learning methods. The findings show that critical thinking, interdisciplinary strategies, and the integration of technology empower students to analyze complex social phenomena. Social studies teachers are essential in facilitating meaningful discussions that highlight the impact of globalization, individualization, and digital transformation. Ultimately, fostering critical thinking within social studies not only deepens students' understanding of social realities but also prepares them to act as reflective, ethical, and responsible agents of change in an ever-evolving society